SHAPING FINANCIAL AND ECONOMIC COMPETENCIES IN THE PROCESS OF TRAINING PERSONNEL FOR THE HOSPITALITY INDUSTRY - LARIONOVA, Anna A.; DZHANDZHUGAZOVA, Elena A.; MINERVIN, Igor G.; YAKIMENKO, Ruslan V.; BALITSKAYA, Irina V. (Journal of Environmental Management and Tourism, 2016)
Relevancy of the issue of shaping financial and economic competencies in the process of personnel training for the hospitality industry is determined by the need to take new requirements for employees of the hospitality industry into account. The purpose of the article is to develop methodological aspects of shaping financial and economic competencies in the process of personnel training for the hospitality industry. The leading approach to the study of this problem is to assess the qualification requirements for the employees of the hospitality industry. The article presents a classification of financial and economic competencies and identifies financial and economic competencies necessary for effective work of employees of the hospitality industry. It is proved that the technology of shaping the applicable financial and economic competencies is based on innovative teaching methods. Since the competencies are generated during the activity, the learning process is built in such a way that students acquire skills in real situations. Examples of active learning tools used in the teaching process are provided. Materials of the article are of practical value to the educational organizations engaged in personnel training for the hospitality industry and the enterprises of this sector.
Keywords: Competency; financial and economic competencies; education; hospitality industry; competence-based approach